Bacteria associated with clinical postpartum dysgalactia syndrome in farmed sows in the Republic of Macedonia - Angjelovski, Branko; Cvetkovikj, Aleksandar; Mrenoshki, Slavcho; Radeski, Miroslav; Cvetkovikj, Iskra; Ratkova, Marija; Dovenski, Toni (The Scientific and Technological Research Council of Turkey, 2016)
The objective of this study was to gather information about the prevalence of bacterial species in farmed sows, with special focus on the clinical manifestation of postpartum dysgalactia syndrome (PDS). One hundred and sixteen sows from 5 pig farms in the Republic of Macedonia were clinically examined for PDS 12–24 h after farrowing. Milk samples and vaginal swabs for bacteriological testing were taken from PDS-affected (PDSA, n = 30) and PDS-unaffected (PDSU, n = 86) sows. Escherichia coli, staphylococci, and streptococci were the predominant bacteria isolates. Escherichia coli was the most frequently found isolate, with a prevalence of 73.3% in PDSA and 31.4% in PDSU sows. Compared to PDSU sows, Escherichia coli was more prevalent in both milk (53.8% vs. 31.4%) and vaginal swabs (74.3% vs. 47.1%) from PDSA sows. Greater prevalence of Escherichia coli in vaginal swabs (66.7%) from PDSA sows suggests that the genital tract represents a possible route for transmission of the infection and that Escherichia coli plays a major role in the development of clinical PDS. Further investigation should be made in order to identify whether specific virulent factors of this bacterium isolated from the genital tract of PDSA sows are associated with clinical occurrence of the syndrome.